Prove that tan A +cot A = sec A cosec A
Answers
Answered by
160
tan A +cot A
sinA/cosA +cos A/sin A
on taking LCM
(Sin²A+cos²A)/sinA cos A
As we know sin²A+cos²A=1
1/sinA cosA⇒cosecA secA {1/cosA=secA, 1/sinA=cosecA}
Hence proved.........................
sinA/cosA +cos A/sin A
on taking LCM
(Sin²A+cos²A)/sinA cos A
As we know sin²A+cos²A=1
1/sinA cosA⇒cosecA secA {1/cosA=secA, 1/sinA=cosecA}
Hence proved.........................
Answered by
7
Given : The given equation is, tan A +cot A = sec A cosec A
To find : To prove the given equation.
Solution :
We can simply solve this mathematical problem by using the following mathematical process. (our goal is to prove the given equation)
Here, we will be using general trigonometric identities.
Working on LHS,
= tan A + cot A
= RHS (proved)
Hence, the given equation (tan A +cot A = sec A cosec A) is proved.
Similar questions
Psychology,
9 months ago
Social Sciences,
9 months ago
Hindi,
9 months ago
Math,
1 year ago
Hindi,
1 year ago
History,
1 year ago